Tanggung Jawab PPAT dalam Peralihan Hak Atas Tanah di Kota Padang - Dilon Scandhiva Ramadi; Azmi Fendri; M. Hasbi (LPPM Universitas Ekasakti Padang, 2023)
The responsibility borne by PPAT is not only to the parties in terms of making land deeds but is also responsible for managing the deed effectively so that it is completed quickly, monitoring land sale and purchase transactions, and carrying out PPAT obligations by PMNA/Kep BPN RI No. 3 of 1997 concerning provisions for the implementation of Government Regulation Number 24 of 1997 concerning land registration as amended by the regulation of the head of the land agency Number 8 of 2012. An empirical juridical approach method was used, where data collection was carried out by field research which can support existing theories after analysis conclusions are drawn. Based on the research results, it was found that there were still PPATs carrying out their duties not based on the provisions of the statutory regulations written above.